Evaluation of a novel biosensor for bioaerosol sampling and modelling. - Jawad, Mohanad Abdulameer (Cranfield University, 2018)
The identification and quantification of bioaerosols in the atmosphere is a significant subject of study. Bioaerosols emitted from composting sites are released directly to the atmosphere, which can be potentially harmful to human health. Although there are several studies undertaken to improve the risk assessment of bioaerosols from composting facilities, this subject still requires further research. Some studies focused on the direct detection of bioaerosol from the composting facilities, and the others focused on the dispersion modelling of bioaerosol. In both cases, the bioaerosol data detected in the direct measurement or the data used in the modelling were dependant on traditional sampling techniques. These techniques provide limited details about the bioaerosol emitted from the composting facilities. These traditional data provide spatial and temporal snapshots of bioaerosol emissions concentrations, and these concentrations represented particular components of bioaerosol. The SIBS (Spectral Intensity Bioaerosol Sensor) is a new sampling device and can provide significant data about bioaerosols, as it can sample continuously over long periods. These advantages made the SIBS able to provide an important picture of the variation of bioaerosol concentrations with time. Several sampling experiments have been done in different environments to measure the bioaerosol concentrations using the SIBS alongside the filtration sampling technique (IOM/SKC). The collected data from the composting site showed the advantages and disadvantages of each sampling technique, and also increased the knowledge of bioaerosol emissions from composting facilities. These novel data were used to calculate emission rates of bioaerosol from agitation activities to improve the output of the bioaerosol dispersion modelling. The results achieved have presented new visions to the current understanding of the characterisation and dispersal of bioaerosols emitted from composting facilities and would be anticipated to make an important contribution to improve the risk assessment of bioaerosol from composting facilities to meet the increased regulatory requirements by Environment Agency.
Keywords: SIBS; IOM/SKC; ADMS; composting; bioaerosols; sampling